The impact of dyadic interventions on psycho-social outcomes for stroke patients and their caregivers: a systematic review and meta-analysis - Xing, Xinyue; Pu, Liping; Hu, Wanyue; Xiao, Yu; Xiao, Hongling (Frontiers in Public Health, 2025)
AimsTo describe the details of dyadic interventions and summarize the current evidence on supporting dyadic interventions for psycho-social outcomes of stroke patients and their caregivers.DesignA systematic review and meta-analysis based on PRISMA guidelines.Data sourcesFive English databases (PubMed, Web of Science, CINAHL, Embase and Cochrane Library) were searched to identify eligible studies published from the inception to October 15, 2024.MethodsTwo reviewers independently screened the literature in accordance with the selection criteria. The risk of bias of the included studies was assessed using Cochrane RoB 2.0. Relevant information was extracted, narrative synthesis was conducted and the meta-analysis was carried out using Review Manager 5.4 soft.ResultsA total of 28 literature were identified and included in this review. These interventions focused mainly on the provision of stroke related knowledge, promotion of family relationships and relief of negative emotions by a face-to-face mode. The outcome indicators can be grouped into three dimensions based on the developmental contextual coping model: dyadic appraisal, dyadic coping and dyadic adjustments. The results of meta-analysis showed that dyadic interventions significantly improved quality of life and coping capacity of patients, promoted family function of caregivers and alleviated caregiver-related burden.ConclusionThese findings highlighted the positive outcomes of dyadic interventions that focused on patients and their caregivers coping with stroke. However, the effectiveness of interventions is not absolute, the evaluation system of intervention effect needs to be improved and demand-driven interventions need to be developed urgently. Therefore, further large-scale randomized controlled trials with a high-quality design are warranted.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, CRD42024621297.